Multiple swallow behaviour during high resolution pharyngeal manometry: prevalence and sub-typing in healthy adults. (2nd January 2022) - Omari, T. I.; Ferris, L.; Schar, M.; Cock, C.; Doeltgen, S.
ABSTRACT: Background: Typical voluntary bolus swallowing consists of a single discrete oropharyngeal swallow. Multiple Swallow Behaviour, such as piecemeal deglutition, is also known to occur in health. We hypothesized that Multiple Swallow Behaviour can be detected and sub-typed utilizing high resolution pharyngeal manometry (HRPM) with impedance . Methods: Prevalence of Multiple Swallow Behaviour was examined in 50 healthy subjects (29 females, mean age 47years, range 19.8–79.5years). HRPM was performed using the Medical Measurement Systems motility system and 8-French pressure-impedance solid state catheter (32 × 1 cm spaced uni-directional pressure sensors, 16 × 2 cm impedance segments). Triplicate boluses of 3, 5, 10 and 20 ml of thin, mildly thick and extremely thick consistencies were tested. Multiple Swallow Behaviour was defined by a sequence of two or more swallows on the pressure topography tracing, occurring after oral bolus administration, with an inter-swallow interval of ≤5 sec. Results: Single swallows were the most common behaviour observed. However, 28 of 50 participants exhibited at least one Multiple Swallow Behaviour event. Larger bolus volumes elicited more Multiple Swallow events. Using impedance, Multiple Swallow Behaviour was further sub-typed as Secondary Dry Swallows (70%, considered normal), Preceding Dry Swallows (1%, considered abnormal), Piecemeal Swallows (25%, considered abnormal for volumes <20 ml) or Clearing Swallows (4%, considered abnormal). Conclusion: HRPM with impedance enables the detection and characterization of Multiple Swallow Behaviour and potentially improves our ability to distinguish manifestations of swallowing disorders. Further studies are required to investigate Multiple Swallow Behaviour sub-types in patients with dysphagia.